2014
DOI: 10.1097/mpa.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy With 177Lu-DOTATATE for Patients With Somatostatin Receptor–Expressing Neuroendocrine Tumors

Abstract: Treatment with multiple cycles of (177)Lu-DOTATATE peptide receptor radionuclide therapy is well tolerated. This treatment results in control of the disease in most patients, whereas systemic toxicities are limited and reversible. Quality of life is also improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 29 publications
4
85
0
1
Order By: Relevance
“…As regards the PRRT, our patient received a dosimetry-based cumulative dose of 30 GBq 177 Lu-DOTATATE without significant bone marrow and kidney toxicity at follow-up. Our results are substantially in line with those of Delpassand et al [11], indicating that treatment with multiple cycles of 177 Lu-PRRT is well tolerated up to a cumulative dose of 29.6 GBq ± 10 %. However, it is still debated whether or not PRRT can be safely used in association with 90 Y radioembolization.…”
Section: Discussionsupporting
confidence: 92%
“…As regards the PRRT, our patient received a dosimetry-based cumulative dose of 30 GBq 177 Lu-DOTATATE without significant bone marrow and kidney toxicity at follow-up. Our results are substantially in line with those of Delpassand et al [11], indicating that treatment with multiple cycles of 177 Lu-PRRT is well tolerated up to a cumulative dose of 29.6 GBq ± 10 %. However, it is still debated whether or not PRRT can be safely used in association with 90 Y radioembolization.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effect of PRRT is best evaluated in a prospective setting. Earlier studies evaluating HRQoL in patients receiving PRRT demonstrated that this treatment actually improves HRQoL in NET patients [29-31] and attenuates symptoms related to the carcinoid syndrome [30-32]. …”
Section: Discussionmentioning
confidence: 99%
“…In principle, the assumption of equidistant administrations with the same activity may limit its application, but it is noted that this is the aimed pattern in the schedule by Gaze et al (2005), and also in other MRT, for instance using 177 Lu-DOTATATE (Delpassand et al, 2014) and 223 Ra-chloride (Lassmann and Nosske, 2013). Although the practical application of the BED formula has been focussed on 131 I-mIBG, it can be applied to other types of fractionated MRT.…”
Section: Discussionmentioning
confidence: 99%